Be Not Afraid!: Building Your Church on Faith and Knowledge - Roberts, Frederic M. (Rowman & Littlefield Publishers, 2005)
In this in-depth study of eight diverse mainline Protestant congregations, anthropologist Fredric Roberts finds that when local congregations are evaluated by spiritual and religious standards instead of corporate- or pop-culture-based values there remains much to celebrate. Roberts recommends that congregations work to discover their own uniqueness and to build upon the strength that already exist among its own members. Be Not Afraid! is a guide to help congregations rediscover their true calling to be nurturing faith communities, committed to spreading the good news and making disciples.